4Ps education 4poor? a critical discourse analysis on beneficiary and government communication practices on the value of education - Rivera, Kristina Clarissa Veron Cruz 1995-; Labor, Jonalou (Quezon City College of Mass Communication, University of the Philippines Diliman, 2016)
"This study aims to understand the communication practices of the beneficiaries and the government, through the FDS Modular Guide, on the value of education in the Pantawid Pamilyang Pilipino Program using Critical Discourse Analyis. Guided by the constructionist grounded theory, the beneficiaries' and government's discourse were analyzed by interviewing unsuccessful and successful saces, their Parent Leader, and conducting a document analysis on the FDS MOdular Guide. The researcher found that both parents use verbal methods such as comparing experiences, reminding the offspring, and reprimanding bad behaviors in order to convey the value of education. Interestingly, the unsuccessful case addressed the Filipino concept of 'hiya' in encouraging the offspring to continue schooling as 'hiya' contributed to the unsuccessful offspring's view on financial difficulties as a reason to stop schooling. Moreover, parents' 'pahiwatig' contributed to the offspring's take on education and its value. Overall the researcher found the unsuccessful case laden with Ochoa's (2014) take on Foucault's punitive practices like physical abuse while the successful case employed non-punitive practices aligned with their messages. Fueled by the government's discourse of top-down educational helping hand, the researcher discovered negative connotations associated with the 4Ps title within the community such as '4Poor' and 'Pantawid Gutom'."
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman